ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMA PADA MATERI BARISAN DAN DERET - Neng Saadah Mardiyah; Gida Kadarisma (IKIP Siliwangi, 2021)
The purpose of this study is to understand the communication skills of high school students in answering the problem of sequences and series. The subjects of this study were students of class XII from high school in West Bandung Regency. The method that the researcher used was descriptive qualitative method. To obtain the data of this study using the interview method and 5 essay questions on mathematical communication skills. Based on the results of this study, it can be said that students' communication skills are still not good or low, especially for the ability to state a situation and daily problems in the form of mathematical patterns and solve them. State a situation or everyday problem in the form of a mathematical model and solve it, State a diagram in the form of a story problem and solve it. The thing that underlies the students do not understand or have correct and good communication skills because students think that writing something they are looking for and knowing is unnecessary. Students still do not understand the concept of sequences and series. Students are still careless in answering questions because they want to finish quickly.